Peran Consumer Engagement dalam Meningkatkan Purchase Behaviour pada Industri Kosmetik Halal: Pendekatan Trust Transfer Theory - Lala Latipah; Yolanda Masnita; Kurniawati Kurniawati (Cakrawala Repositori IMWI)
The development of digital technology has changed consumer behavior in purchasing halal cosmetics through increased trust in digital platforms, the use of AI Beauty Influencers, and the sensory experiences offered by brands. However, research results on the role of Consumer Engagement in bridging this relationship still show mixed findings. This study aims to analyze the influence of Digital Trust, AI Beauty Influencers, and Sensory Marketing on Purchase Behavior among halal cosmetic consumers in Indonesia, with Consumer Engagement as a mediating variable based on Trust Transfer Theory. The study used a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Data were collected through an online questionnaire from 200 respondents selected using a purposive sampling technique. The results showed that Digital Trust, AI Beauty Influencers, Sensory Marketing, and Consumer Engagement have a positive and significant effect on Purchase Behavior. Conversely, Sensory Marketing does not have a significant effect on Consumer Engagement, so Consumer Engagement is unable to mediate the effect of Sensory Marketing on Purchase Behavior. This finding strengthens Trust Transfer Theory, which states that trust in digital information sources and AI Beauty Influencers can be transferred into trust in products, thereby increasing consumer purchasing behavior. This research provides practical implications for halal cosmetic companies to strengthen digital trust, utilize credible AI Beauty Influencers, and optimize sensory marketing strategies to improve consumer purchase behavior.